Early Onset of Franciscan Subduction. Issue 5 (5th May 2018) - Mulcahy, Sean R.; Starnes, Jesslyn K.; Day, Howard W.; Coble, Matthew A.; Vervoort, Jeffrey D.
Abstract: The Franciscan subduction complex of California is considered a type example of a subduction‐accretion system, yet the age of subduction initiation and relationship to the tectonic history of western North America remain controversial. Estimates for the timing of Franciscan subduction initiation are largely based either indirectly on regional tectonic arguments or from the ages of high‐grade blocks within mélange. Many of the high‐grade blocks record counterclockwise pressure‐temperature paths with early amphibolite overprinted by later eclogite and blueschist; however, their origin and significance with respect to subduction initiation have been debated. In contrast, some high‐grade blocks show evidence for clockwise pressure‐temperature paths and an early eclogite assemblage overprinted by later amphibolite. Zircon U‐Pb ages from inclusions in garnet and Lu‐Hf estimates of initial garnet growth ages from these samples record early eclogite metamorphism at ~176 Ma. Matrix zircon U‐Pb ages and Lu‐Hf estimates of final garnet growth ages record a barroisite‐amphibolite assemblage overprint of eclogite at ~160 Ma. Combined with petrologic data and existing geochronology, the data suggest that (1) Franciscan subduction was underway by no later than 180 Ma, (2) continuous subduction metamorphism occurred for at least 100 Ma, and (3) Franciscan subduction initiation predated the formation of the overlying Coast Range Ophiolite, supporting models that form the ophiolite above an east dipping Franciscan subduction zone. Plain Language Summary: Subduction zones are places where dense ocean crust descends (or subducts) beneath more buoyant plates of continental or oceanic crust. Ancient subduction zones exposed at the Earth's surface provide important information on past plate movements and processes now occurring within active subduction zones. Determining the age that subduction began in ancient subduction zones is difficult because the earliest formed rocks are rarely preserved in the rock record. Our study focuses on the Franciscan Complex of California, which is considered a type example of an ancient subduction zone. The timing of Franciscan subduction initiation, however, has long been debated, resulting in conflicting models for the tectonic history of western North America. This study is unique because we dated the mineral zircon preserved as inclusions within garnet formed during the early stages of subduction. We also analyzed zircon outside of garnet formed during a younger event within the subduction history. The zircon inclusions within garnet yield an age of ~176 Ma, whereas the zircon outside the garnet had a younger age of ~160 Ma. These ages require that Franciscan subduction began by 180 Ma, significantly older than commonly believed and constrain models for the tectonic evolution of the western North American margin. Key Points: Franciscan subduction began by about 180 Ma and continued as a single, long‐lived, east dipping subduction zone for approximately 100 Ma The metamorphic history of high‐grade blocks reflects several processes that operated at different times and places in the subduction zone Franciscan subduction is older than the Coast Range Ophiolite, which likely then formed above an east dipping Franciscan subduction zone